Structure and photoluminescence properties of PbO–Bi2O3–Ga2O3 glass-ceramics containing silver nanoparticles, free lead and bismuth ions (2023)
We report the synthesis, structural characterization, and optical properties of PbO–Bi2O3–Ga2O3 glass-ceramics (GCs) containing PbO and Bi2O3 crystallites, free lead (Pb2+) and bismuth (Bi3+) ions, and silver nanoparticles (Ag-NPs). The samples were prepared by applying the melt-quenching method followed by suitable heat-treatment of the samples. Transmission Electron Microscopy, X-ray diffraction, linear optical absorption, and photoluminescence (PL) were the techniques applied to characterize the samples. When the samples were excited at 330 nm a large PL intensity, due to the Pb2+ and Bi3+, is observed. Moreover, large PL intensity enhancement of about 1000% for the samples containing Ag-NPs is observed in comparison with the PL intensity from the samples without Ag-NPs. This is the first time that this behavior is reported for a GCs based on heavy-metal oxides. The potential of this class of materials for photonic applications is discussed.